2021
DOI: 10.3389/fnbeh.2021.695409
|View full text |Cite
|
Sign up to set email alerts
|

Social Housing Leads to Increased Ethanol Intake in Male Mice Housed in Environmentally Enriched Cages

Abstract: An individual's social environment affects alcohol intake. However, the complex interactions between social context and alcohol intake remain understudied in preclinical models. In the present study, we sought to characterize the effects of social housing on voluntary ethanol intake in male C567BL/6J mice using a continuous access two-bottle choice model. This was accomplished using HM2 cages, which allow for the continuous monitoring of individuals' fluid intake through radiofrequency tracking while they rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
(34 reference statements)
1
9
0
Order By: Relevance
“…This continued for 2 days, after which, 3% ethanol bottles were swapped to 6% ethanol in autoclaved water for the next 3 days ( Figure 1E ). We did not use higher concentrations of ethanol because our previous experiments indicated that mice strongly reduced intake of ethanol in HM2 cages when higher than 6% solutions were used ( Caruso et al, 2021 ; Fulenwider et al, 2021 ). In standard shoebox cages, the position of ethanol and water bottles were swapped daily to avoid side preference bias.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This continued for 2 days, after which, 3% ethanol bottles were swapped to 6% ethanol in autoclaved water for the next 3 days ( Figure 1E ). We did not use higher concentrations of ethanol because our previous experiments indicated that mice strongly reduced intake of ethanol in HM2 cages when higher than 6% solutions were used ( Caruso et al, 2021 ; Fulenwider et al, 2021 ). In standard shoebox cages, the position of ethanol and water bottles were swapped daily to avoid side preference bias.…”
Section: Methodsmentioning
confidence: 99%
“…Although the overall number of licks in lickometer cages correlates with alcohol drinking in many studies ( Ford et al, 2005 ; Griffin et al, 2007 ; Anacker and Ryabinin, 2013 ), lick sizes may differ across various fluids, circadian phases, or experimental conditions. To circumvent this potential problem, we have recently adopted the tracking of consummatory behaviors using radio frequency identification (RFID) tags in Heardsman-2 (HM2) cages ( Thomsen et al, 2017 ; Caruso et al, 2021 ; Fulenwider et al, 2021 ; Walcott and Ryabinin, 2021 ). The HM2 cages are typically large, allowing group housing of rodents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During surgical recovery and behavioral studies, mice were individually housed without any environmental enrichment. Single-housing was necessary to get accurate measurements of individual drinking as well as because both social dynamics (Fulenwider et al, 2021) and environmental enrichment can impact ethanol consumption (Holgate et al, 2017). The procedures used in this study were all approved by the University of North Carolina Institutional Animal Care and Use Committee and followed the Guidelines for the Care and Use of Laboratory Animals (National Research Council, 2011).…”
Section: Methods Animalsmentioning
confidence: 99%
“…The copyright holder for this preprint (which this version posted May 23, 2024. ; https://doi.org/10.1101/2024.05.22.595186 doi: bioRxiv preprint cage (Panksepp et al, 2017). Specialized housing environments, such as the IntelliCage (Holgate et al, 2017) and HM2 cage (Fulenwider et al, 2021), have been valuable tools in studying the efects of social housing and enrichment on consummatory behavior. However, these systems are costly and require specialized housing.…”
Section: Introductionmentioning
confidence: 99%